PHANTOM OF THE LIBRARY - Terrell, Brandon, 1978-; Epelbaum, Mariano, 1975- (North Mankato, Minnesota : Stone Arch Books, a Capstone imprint, 2018)
The Ghost Grabbers (an internet program, and Jaden's heroes) are filming a seance at the Pendleton Public Library, where the recently discovered unpublished manuscripts of the late horror author and library founder Alistair Pendleton are on display--so when the lights go out, and the manuscripts disappear, Jaden (who thinks a ghost took them), his twin sister Hayden, and the other members of Snoops Inc. swing into action to solve the myster
Keywords: Children's stories, English; English fiction; Public libraries -- Fiction